From bordered land, to borderland, and back again: how the Sangre de Cristo Land Grant became part of the United States, 1844-1878 - Swisher, Jacob, author; Orsi, Jared, advisor; Little, Ann, committee member; Duffy, Andrea, committee member; Payne, Sarah, committee member (Colorado State University. Libraries, 2020)
From 1844 to 1878, the Sangre de Cristo Land Grant, a one-million-acre parcel in Colorado and New Mexico's San Luis Valley, experienced a transition from a Ute landscape, to a Ute, Nuevomexicano, and American borderland, and, finally, to an American region. This rapid, thirty-year transformation centered on conflicts between Utes, Nuevomexicanos, and American and European migrants and land speculators over the grant's borders, including legal, racial, political, economic, and scientific ones. By 1878, the outcome of these border contests was a relatively stable, bordered landscape on the Sangre de Cristo Land Grant. Examining this transition as a shift from a Ute bordered land, to a Ute, Nuevomexicano, and American borderland, and, finally, into a bordered, American region not only demonstrates that border contests were central to the expansion of the United States and its settler populations across the American West but also shows how contests over borders have offered important avenues of resistance for local communities in the San Luis Valley in both the past and present.